Growing Strawberries in the Florida Home Garden - Craig K. Chandler; James F. Price; Natalia A. Peres; Bielinski M. Santos (EDIS)
HS-1154, a 4-page illustrated fact sheet by Craig K. Chandler, James F. Price, Natalia A. Peres, and Bielinski M. Santos, provides home gardeners with information about strawberry growing conditions and varieties for Florida, soil preparation and plant establishment, freeze protection, pest management, and harvesting and storage. It replaces HS509/VH029, Strawberries in the Florida Garden, by James M. Stephens. Published by the UF Department of Horticultural Sciences, December 2008.